A Comparative Analysis Between Good Feedback Descriptors on Online Courses - Cavalcanti, Anderson Pinheiro; Rolim, Vitor Belarmino; Gašević, Dragan; Mello, Rafael Ferreira (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2023.235316, 2023)
Feedback is a critical component of the teaching-learning process. Through it, teachers share relevant information so that students understand the subjects and activities, in addition to promoting self-regulation. However, the activity of writing and sharing feedback is not easy and may even lead to students’ demotivation. Given this, it is possible to find several works in the educational research literature that propose good practices for elaborating textual feedback. This work aims to analyze the relationship between different models of good practices for feedback and the relationship between English feedback and Portuguese feedback using an epistemic network (ENA). The results show that some characteristics are similar, but the models do not have a direct relationship. It is concluded that a combination of these models can improve the analysis of feedback quality.